Improved Watermarking Leach Protocol using node level Integrity and Confidentiality in WSN - Rani, Rekha; Manro, Rajan (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor network is a network which consists of number of sensor nodes which sense the data and send to sink node. As detecting sensor data with defective readings is an important issue for secure communication. So, necessity of privacy and integrity of information is mandatory. Thus, cryptography is an effective technique that provides privacy and integrity to sensed data. This paper, deals with the improvement of watermarking LEACH with node level data integrity and confidentiality.